ChemInform Abstract: Rh(III)‐Catalyzed Oxidative Coupling of Benzoic Acids with Geminal‐Substituted Vinyl Acetates: Synthesis of 3‐Substituted Isocoumarins. Issue 21 (May 2015) - Zhang, Mingliang; Zhang, Hui‐Jun; Han, Tiantian; Ruan, Wenqing; Wen, Ting‐Bin
Abstract Both 3‐aryl and 3‐alkyl substituted isocoumarins are synthesized by a Rh(III)‐catalyzed C—H activation/annulation reaction of electron‐rich germinal‐substituted vinyl acetates and arylcarboxylic acids.